Pengaruh Kepemimpinan Transformasional Terhadap Perilaku Kerja Inovatif di Tempat Kerja: Efek Moderasi dari Dukungan Organisasi yang Dirasakan dan Keterlibatan Kerja: Studi Penelitian pada karyawan di PT.H - Nadia Rahmawati; Achmad, Nur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of transformational leadership on innovative work behavior, considering the moderating effects of perceived organizational support and work engagement among employees of PT.H. The research employed a quantitative method with SEM-PLS analysis, involving 57 respondents selected through purposive sampling. Primary data were collected using a questionnaire designed to measure the research variables. The results indicate that transformational leadership has a significant positive effect on innovative work behavior, suggesting that leaders who adopt this leadership style can encourage employees to innovate and contribute creatively in the workplace. However, the analysis also revealed that perceived organizational support and work engagement do not significantly moderate this relationship. This finding implies that, while support and engagement are important, the impact of transformational leadership on innovative behavior remains strong regardless of these factors. Understanding that transformational leadership can independently enhance innovative behavior, companies are advised to focus on strengthening leadership styles to create a work culture that supports innovation. This research also opens opportunities for further studies on other factors that might influence the relationship between leadership and innovation in organizational settings.